Creating an Awareness Campaign Against the Fomo Phenomenon in Young Adults’ Social Media Usage - Vera Jenny Basiroen; Adinda Hapsari (Bina Nusantara University, 2018)
This research aimed to create an awareness campaign on raising the understanding of the topic as prevention toward the happiness and productivity-killing phenomenon or FoMO (Fear of Missing Out) phenomenon in young adults’ social media usage. Qualitaive method was applied in the research by (1) using questionnaire; (2) interviewing the psychological experts; (3) using secondary research such as books, journals, printed articles, and online sources. Then, the researchers drew a solution by analyzing the collected data. The distribution also focused on people who were active users of social media. This research finds that promoting positive thoughts in people who experience FoMO might be an effective solution to combat this type of anxiety. Therefore, the data become the underlying basis toward the making of SayNomoToFomo campaign. Its main strategy is to educate and encourage the target audience to understand and tackle FoMO using a mixture of interactive and printed medium.